Cloning and Sequence Analysis of Wild Argali ISG15 cDNA - Sun, Yanming (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2014)
The complete coding sequence of Wild Argali ISG15 cDNA was generated by rapid amplification of cDNA ends. The ISG15 cDNA was 642 bp with an open reading frame of 474 bp, which encoded a 17.47 kDa protein composed of 157 amino acids. Its amino acid sequence shared 97.9%, 80.8%, 91.4%, 94.3%, 78.3% identity with those of ISG15cDNA from Ovis aries (accession no. NM001009735.1), Capra hircus (accession no. HQ329186.1), Bos taurus (accession no. BC102318.1), Bubalus bubalis (accession no. HM543269.1), and Sus scrofa (accession no. EU647216.1), respectively. The entire coding sequence was inserted into the pET-28a vector and expressed in E. coli. The recombinant protein corresponded to the expected molecular mass of 25 kDa as judged by SDS-PAGE, and it was detected in the bacterial inclusion bodies. The expressed protein could be purified by Ni(2+) chelate affinity chromatography and the results from the lymphocyte proliferation test showed that the product could stimulate lymphocyte proliferation very well (p<0.05), which further confirmed its biological activity.